Neutron reflector analysis for the beam-port of the Missouri S&T Reactor - AKYÜREK, TAYFUN (SPRINGER, 2019)
A preliminary neutron reflector material selection and feasibility study of an inexpensive reflector replacement for the neutron beam-port at the 200 kW Missouri University of Science and Technology Research Reactor (MSTR) was conducted using Monte-Carlo techniques. The Monte-Carlo N-Particle transport code (MCNP6.1) was used to model the neutron beam-port of the Missouri S&T Reactor in order to study the effects of adding different reflector materials, in terms of the neutron flux reaching the radiography/tomography facility in front of MSTR's neutron beam-port. Aluminum, beryllium, titanium, nickel, nickel-58, lead, bismuth, tungsten and stainless steel reflectors were modeled to find the best neutron reflector for the beam-port. After examining reflector materials, it was concluded that none of them were an improvement over the current design. Experimental thermal flux was measured to be 1.0 x 10(7) +/- 3.16 x 10(3) cm(-2) s(-1) at the exit of beam port for current version of beam-port. The current ratio of beam port inlet and outlet obtained from simulations was found to be 3.37 x 10(4). The flux of beam port inlet was determined on the order of 1.0 x 10(11) cm(-2) s(-1) which is consistent with previous findings.
Keywords: Inexpensive neutron reflector; Neutron beam-port; Monte Carlo N-Particle (MCNP); UNIVERSITY; SPECTRUM; VALIDATION; SYSTEM